The Relationship Between Role of Family with Choice of Therapy at Degenerative Elderly Peoples Iha Suco Horai Quik Posto Administrativo Maubesse Municipiu Ainaro Tinan 2024 - Yanto, Yoseph Uli; Owa, Maria Goreti; Ningtyas, Rahaju; Ximenes, Manuela Do Rosario S. S.; Moreira, Faviao Marcal; Hendriques, Surly Edgar Faria Reis (Al-Hijrah Indonesia, 2024)
Degenerative conditions in the elderly impact their psychological and social well-being. Lack of knowledge regarding alternative therapy options also results in families more often choosing pharmacological therapy as the main solution. This study aims to analyze the relationship between the role of the family and the choice of therapy in the elderly with degenerative conditions at Suco Horai Quik Posto Administrativo Maubesse Municipiu Ainaro Tinan 2024 and identify factors that support and hinder the choice of therapy by the family. This study used a quantitative approach with a cross-sectional design. The sample consisted of families caring for older adults with degenerative conditions in Suco Horai Quik Posto Administrativo Maubesse Municipiu Ainaro. Data were collected through questionnaires covering the variables of family role, choice of therapy, and supporting or inhibiting factors in decision-making. The results showed that the role of the family in supporting the elderly with degenerative conditions in Suco Horai Quik, Posto Administrativo Maubesse, Munisipiu Ainaro was mainly categorized as good, with 116 or (67.4%) of respondents. The most widely used treatment option was pharmacological, with 108 (62.8%) respondents. Supporting factors for therapy selection included family support, with 103 (59.9%) respondents, as well as the level of awareness and health education with 117 (68.0%) respondents. Barriers included adequate access to health services (62.2%), affordable treatment costs (66.9%), and sufficient knowledge of treatment options (65.7%). The analysis showed a significant relationship between family roles and treatment options in the elderly and between family support as caregivers, awareness raising and health education, and limited access to health services with treatment options. In conclusion, family roles were shown to influence the choice of therapy for the elderly significantly. In contrast, other factors such as family support, awareness raising, and knowledge did not significantly influence the choice of therapy in several other categories.